Evaluasi Penggunaan Dana Desa dalam Pembangunan Infrastruktur Perdesaan: Studi Kasus di Provinsi Lampung - Mustika Wulandari; Pradita Mawardani; Zaqi Rohman; Suci Hayati (Teewan Journal Solutions, 2025)
This study aims to evaluate the use of village funds in rural infrastructure development in Lampung Province. Using a descriptive qualitative approach through literature review, the research analyzes various official documents, government reports, and relevant previous studies. The findings indicate that the increase in village fund allocation from 2016 to 2018 had a positive impact on infrastructure development, such as village roads, irrigation channels, and other public facilities. However, the effectiveness of fund utilization is still influenced by several internal village factors, including human resource capacity, the functionality of village institutions, and community involvement. The main challenges in managing village funds include the lack of technical training for village officials, weak oversight systems, and limited public participation in the development process. Therefore, it is necessary to enhance the capacity of village officials, strengthen accountability systems, and optimize community participation to ensure that rural infrastructure development can be carried out more effectively, efficiently, and sustainably.